REVITALISASI TASAWUF DI MASA MODERN - Gina Giftia Azmiana; Abdul Kadir; Yuningsih Yuningsih (JURNAL ISTEK, 2012)
The reality view of some Moslems today in regard to Sufism is conservative, old-fashioned or even something which is not comes from Islam. On the other hand, modern life which is characterized with materialism, rationalism, and hedonism not only brings positive value to development of science and technology but also negative effects to human being. Human life becomes empty and detached from spirituals values. Eventually, acts of worship (Ibadah) that Moslems perform merely just a ritual that does not impact positively to personal piety or society. Therefore, revitalization of Sufism is aimed to reinstate the importance of Sufism for Moslems life with understanding the nature of Sufism itself. The essence of Sufism is to present Allah in every aspects of life. Commencing with learn to love, then improving the quality of life by loving something which is the most entitled to be loved, which is Allah. At the same time the interpretation of Zuhud is going through by putting into effect on daily life as a way to get the best place in the Hereafter as well as Allah's approval.